Handbook of research on contemporary consumerism - Kaufmann, Hans Rüdiger 1958-; Mohammad Fateh Ali Khan Panni 1981- (IGI Global, 2020)
"This book is a comprehensive reference source on new innovative dimensions of consumer behavioral studies and reveals different conceptual and theoretical frameworks. Featuring expansive coverage on a number of relevant topics and perspectives, such as green products, automotive technology, and anti-branding"--
Keywords: Consumption (Economics); Consumer behavior